Informal settlement dwellers and environmental problems . - Muzvidziwa, Victor N. (2016)
Past and current experiences indicate that informal settlements will persist for quite sometime. The paper adopts the use of informal settlements to avoid negative connotations associated with other terms. Informal settlements as a term is defined quite elaborately in the paper, however, what further elucidates the definition are the key informal settlement issues and challenges related to the environment; living conditions in informal settlements; access to urban housing and environmental concerns; land tenure and property rights and; land invasions. Solutions to these issues and challenges are imperative to address the host of environmental concerns they create. Several ideas towards addressing particularly urban low-income housing have had very marginal successes and these include: the laissez-faire attitudes of 1950-1960s; the site and services of 1970s spear-headed by the World Bank for enabling shared responsibility between government and informal settlement dwellers; the slum upgrading programmes of 1980s which put emphasis on provision of communal infrastructure and services within established informal settlements; enabling and security of tenure strategies of the 1990s which emphasised on the sustainability of housing development programmes; and the recent “ Cities without slums” action plan in the 2000s which targets the improvements of living conditions of urban dwellers while questioning the prevalence and persistence of poverty in informal settlements.